CAN FAMILIES BE ABLE TO RECOGNIZE SIGNS AND SYMPTOMS OF ACUTE CORONARY SYNDROME? CAN FAMILIES BE ABLE TO RECOGNIZE SIGNS AND SYMPTOMS OF ACUTE CORONARY SYNDROME? - Aziz, Aditya Nuraminudin Nuraminudin (Well Being, 2020)
Acute coronary syndrome (ACS) is one of the problems of cardiovascular which is the cause of increased mortality rates. Treatment in patients with ACS should be done immediately, acute myocardial infarction can lead to death, so it needs the ability to assess the signs and symptoms of ACS. One of the family's roles in supporting the exactness of treatment is being able to recognize the signs and symptoms of the acute coronary syndrome. Based on this, researchers are interested to know how the family's ability to recognize the signs and symptoms of ACS. The research method used in this research is qualitative with a descriptive phenomenological design approach. The study uses in-depth interviews involving 8 participants. In this study acquired 2 themes depicting the ability of the family in recognizing the signs and symptoms of ACS is ignorance about the symptoms of ACS and errors in recognizing the symptoms. Family members who do first aid in ACS patients often have errors in interpreting the signs and symptoms of ACS, these signs and symptoms are often interpreted as diseases that have been suffered by ACS patients.